PENGGUNAAN STIMULAN DALAM PENYADAPAN PINUS - Sukadaryati; Gunawan Santosa; Gustan Pari; Dodik Ridho Nurrochmat; Hardjanto (BRIN Publishing, 2014)
For the formulation of policy strategies on the use of environmentally friendly stimulant in the production of pine resin, the study of innovation stimulant is a necessity. This study aimed to identify the use of stimulants made from a strong acid (inorganic), ETRAT and wood vinegar on pine tapping. Research results revealed that the use of stimulants could increase resin flux and extend. Inorganic stimulant produced resin more than ETRAT and wood vinegar per collection in area with elevation above 500 ASL and below 500 ASL. The use of inorganic stimulant, however, caused the change of wood colour that will be dark brown to reddish even that going into as far as to the pith of wood. Meanwhile, the use of organic stimulant doesn't cause the change of colour in wood significantly. Therefore the use of stimulants on tapping pine needs to consider the negative effects of trees's health, workers and the environment.The economic aspect that should be persued to achieve the financial target, is not the main factor only but the ecological and sosial aspects to achieve a yield sustainability and tree producing are requared.